Algorithms and Architectures for Parallel Processing
DOI: 10.1007/978-3-540-69501-1_14
|View full text |Cite
|
Sign up to set email alerts
|

Parallel Simulated Annealing for Materialized View Selection in Data Warehousing Environments

Abstract: In order to facilitate efficient query processing, the information contained in data warehouses is typically stored as a set of materialized views. Deciding which views to materialize represent a challenge in order to minimize view maintenance and query processing costs. Some existing approaches are applicable only for small problems, which are far from reality. In this paper we introduce a new approach for materialized view selection using Parallel Simulated Annealing (PSA) that selects views from an input Mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0
3

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 15 publications
0
41
0
3
Order By: Relevance
“…Randomize algorithms such as simulated annealing algorithms [7,8,14] and genetic algorithms [5,13,18,30,16] have been used and explored for the selection of materialized views in order to improve the quality of the solution. These algorithms use a randomized search strategy for deciding which views to materialize.…”
Section: Randomized Algorithms Based Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Randomize algorithms such as simulated annealing algorithms [7,8,14] and genetic algorithms [5,13,18,30,16] have been used and explored for the selection of materialized views in order to improve the quality of the solution. These algorithms use a randomized search strategy for deciding which views to materialize.…”
Section: Randomized Algorithms Based Methodsmentioning
confidence: 99%
“…We have implemented our approach and compared it with a randomized method because in previous studies [30,7,8], it was shown that randomized algorithms provide a significant improvement in the performance compared to deterministic algorithms. The most commonly used randomized algorithms in the context of view selection are simulated annealing algorithms and genetic algorithms.…”
Section: Experimental Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…Another using of simulated annealing for materialized view selection has been proposed in [11] in which a parallel simulated annealing algorithm selecting views from an input MVPP. Although the combination of parallel simulated annealing and MVPP has been resulted in increasing the quality of obtained set of materialized views and improving the query processing time and decreasing view maintenance cost, it trapped to local minimum in some cases.…”
Section: Related Workmentioning
confidence: 99%
“…Também podem existir vários níveis intermediários entre os níveis superior e inferior, representando graus crescentes de agregação (Agrawal et al, 2000;Baralis et al, 1997;Derakhshan et al, 2008;Gupta e Mumick, 1999;Harinarayan et al, 1996;Hung et al, 2007;Kotidis e Roussopoulos, 2001;Lawrence e Rau-Chaplin, 2006;Shah et al, 2006).…”
Section: Níveis De Agregaçãounclassified